Impuesto a las embarcaciones de recreo - Ruiz de Castilla Ponce de León, Francisco Javier (2013)
Tax Law attempts to regulate the majority of possible circumstances, in order to achieve an effective taxing on what requires be taxed. Being the acquisition of recreational boats an increasingly frequent phenomenon, it’s necessary to apply the Tax to Recreational Boats and to understand this tax in the light of the Peruvian legislation. On this occasion, the author analyzes the current situation of the imposition to these movable goods, through the interpretation and even questioning of its legal basis: the Law of Municipal Taxation and the regulation of the Tax to Recreational Boats.